Korelasi Antar Tingkat Kerusakan Bangunan Akibat Gempa pada Sistem Struktur Reinforced Concrete Sebagai Preferensi Arsitek - Rita Laksmitasari Rahayu; Yulita Hanifah (MAESTRO, 2022)
Indonesia is one of the countries that have the potential to experience an earthquake. Most of the high-rise buildings use a reinforced concrete structural system design. Architects need to understand the level of damage to non-structural elements that affect the level of damage to structural elements in buildings that use reinforced concrete structural system designs. The research method used is a quantitative method by looking for a relationship or correlation between the level of damage to structural elements and the level of damage to non-structural elements. In the early stages, this research uses data processing techniques - document content analysis. Documents are analyzed systematically, integrated, and intact. The next stage, the results of the analysis of the contents of the document are used as data in the next process, namely looking for relationships between variables that have been found. The purpose of this study was to find a relationship between the level of damage to non-structural elements and the level of damage to structural elements in buildings with a reinforced concrete structural system design. The results of the study found a relationship between the level of damage to non-structural elements and the level of damage to structural elements for buildings with reinforced concrete designs. The novelty obtained in this study is that the building did not experience damage to structural elements but tended to have slight damage to non-structural elements leading to moderate damage. Recommendations for architects are buildings with reinforced concrete structural system designs that require building stiffeners (core, bracing, shear wall) as structural elements.